2016
DOI: 10.1155/2016/8603409
|View full text |Cite
|
Sign up to set email alerts
|

5HT3 Antagonists versus Dexamethasone in the Prevention of PONV in Patients Undergoing Laparoscopic Cholecystectomy: A Meta-Analysis of RCTs

Abstract: Background. 5HT3 antagonist, an antiemetic alternative to dexamethasone, is an effective drug for the prevention of postoperative nausea and vomiting (PONV). Methods. PubMed and The Cochrane Library (from inception to June 2016) were searched for relevant RCTs (randomized controlled trials). Results. Seven trials, totaling 682 patients, were included in this meta-analysis. This meta-analysis demonstrated that 5HT3 antagonist was as effective as dexamethasone in preventing PONV (RR, 1.12; 95% CI, [0.86, 1.45]; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The antiemetic effect of propofol is attributed to modulation of subcortical pathways to inhibit nausea or its direct depressant action on the vomiting center [ 29 ]. The results of our study are consistent with other studies, conducted in different settings, in terms of antiemetic rescue therapy requirements and trends of dexamethasone preventive effect [ 22 , 23 , 25 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The antiemetic effect of propofol is attributed to modulation of subcortical pathways to inhibit nausea or its direct depressant action on the vomiting center [ 29 ]. The results of our study are consistent with other studies, conducted in different settings, in terms of antiemetic rescue therapy requirements and trends of dexamethasone preventive effect [ 22 , 23 , 25 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Glucocorticoids have been widely used to prevent PONV during chemotherapy use or general anesthesia. Although the antiemetic mechanism is not clearly understood, scientific evidence suggests that dexamethasone reduces production and release of 5-HT and decreases permeability across the Blood-Brain Barrier (BBB) thereby lowering the amount of 5-HT available to chemical sensors [ 18 , 25 ]. However, the use of dexamethasone may be associated with increased risk of infection, reduced wound healing, and interference with the functioning of adrenal glands through negative feedback-mediated reduction of endogenous steroid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 18 The combination of tropisetron (a 5-HT 3 receptor antagonist) with methylprednisolone sodium succinate in solutions to relieve chemotherapy-induced nausea and vomiting is now accepted, but there have been no reports to date about the compatibility and stability of such mixtures for clinical practice. 19 Therefore, the present study aims to address this issue. As mentioned previously, many studies have tested the stability and compatibility of methylprednisolone sodium succinate alone or in combination with other drugs in infusion solutions and suggested that methylprednisolone sodium succinate is a very stable drug.…”
Section: Discussionmentioning
confidence: 98%
“…The exact mechanism of action of dexamethasone remains unclear. An explanation might be the effects of dexamethasone on the vomiting center at the medulla oblongata and central nervous system, such as blood-brain-barrier permeability alterations to some blood proteins, changes in neurotransmitters activity, such as serotonin and dopamine, or suppression of prostaglandins production (10,13).…”
Section: Introductionmentioning
confidence: 99%